Exploring Vietnamese Pre-Service Teachers’ Knowledge, Attitudes, Beliefs, and Teaching Intentions Regarding Climate Change - Thao Phuong Nguyen; Thuy Thi Ha; Nu Thi Dang; Binh Thi Pham; Chu A Trang; Thao Thu Thi Trinh (Vietnam Journal of Education)
Climate change presents significant global challenges and is a top priority for many countries, including Vietnam, in achieving sustainable development goals. Teachers’ perceptions of climate change strongly influence their teaching and ability to inspire students to take actions. This study examines the knowledge, attitudes, beliefs, and teaching intentions of Vietnamese pre-service teachers regarding climate change through a survey of 468 participants from teacher education institutions nationwide. Research findings reveal that while pre-service teachers have some understanding of climate change, their knowledge remains limited. Although most express a willingness to act, their beliefs about climate change are often ambiguous and inconsistent. This study represents the first large-scale survey in Vietnam on this topic, providing implications for teacher education programs. Specifically, integrating climate change education as a mandatory course or shared module, incorporating experiential learning, ensuring access to updated research, and enhancing institutional support are crucial for strengthening pre-service teachers’ knowledge and confidence in educating about climate change.